Peningkatan Kelompok Sadar Wisata (Pokdarwis) di Dusun Thekelan, Desa Getasan, Kecamatan Batur, Kabupaten Semarang - Indah Fajarini Sri Wahyuningrum; Muhammad Ihlashul Amal; Niswah Baroroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2020)
Abstract Thekelan Hamlet, Batur Village, Getasan District, Salatiga City has extraordinary tourism potential. This village has many tourist objects that can be enjoyed, and the residents' socio-cultural conditions are very supportive. The location of Thekelan Hamlet is at an altitude of ± 2000 meters above sea level with extraordinary views and is surrounded by protected forest areas, making the social characteristics of the community homogeneous and distinctive with a strong highland culture. In 2018 Thekelan hamlet succeeded in forming the Mahardika Tourism Awareness Group (Pokdarwis), where this pokdarwis can produce several tour packages offered to tourists, including live-in programs. Thekelan hamlet receives visits from universities and schools every year for comparative study activities and the live-in program. However, the problem is that the community is only involved in providing accommodation and consumption, where the average turnover is around Rp. 30,000, - to Rp. 50.000, - per person. Therefore, it is necessary to increase tourism activities in the promotion and management sector of Pokdarwis Mahardika through increasing the hard skills and the soft skills of POKDARWIS MAHARDIKA managers. This community service aims to increase public awareness in managing tourism in the Thekelan hamlet. This increased awareness is expected to be able to improve the economy of the surrounding community. The training method uses lecture, practice, and intensive mentoring methods. This community service aims to increase tourism management in the Thekelan hamlet. The increasing number of tourism management around Thekelan hamlet is expected to be able to improve the economy of the surrounding community by increasing the level of tourist arrivals. The training method uses lectures, practice and intensive mentoring. Abstrak Dusun Thekelan, Desa Batur, Kecamatan Getasan, Kota Salatiga memiliki potensi wisata yang sangat istimewa. Desa ini memiliki banyak objek wisata yang bisa dinikmati serta kondisi sosial budaya warga sangat mendukung. Letak Dusun Thekelan berada di ketinggian 2000 mdpl dengan pemandangan yang luar biasa, dan dikelilingi oleh kawasan hutan lindung membuat karaketeristik sosial masyarakat bersifat homogen dan khas dengan kultur budaya dataran tinggi yang kuat. Pada tahun 2018 dusun Thekelan berhasil membentuk Kelompok Sadar Wisata (Pokdarwis) Mahardika dimana pokdarwis ini dapat menghasilkan beberapa paket-paket wisata yang ditawarkan pada wisatawan diantaranya program live in.. Dusun Thekelan sebenarnya setiap tahun telah menerima kunjungan dari universitas maupun sekolah untuk kegiatan studi banding maupun program live in. Namun permasalahannya, masyarakat hanya terlibat dalam pengadaan tempat penginapan dan konsumsi di mana rata-rata omset yang masuk masih terhitung sedikit. Oleh karena itu, perlu adanya peningkatan kegiatan wisata dalam sektor promosi dan menajemen dari Pokdarwis Mahardika melalui peningkatan hardskill dan softskill para pengelola POKDARWIS MAHARDIKA. Pengabdian masyarakat ini bertujuan untuk meningkatkan pengelolaan wisata di di dusun Thekelan. Adanya peningkatan pengelolaan pariwisata di sekitar dusun Thekelan diharapkan mampu meningkatkan perekonomian masyarakat sekitar melalui meningkatnya tingkat kedatangan wisatawan. Metode pelatihan menggunakan metode ceramah, praktik dan pendampingan intensif.